Erratum to: Local Structure of Lead-containing Mixed-ion Perovskite Ferroelectrics Studied Using Neutron Total Scattering Analysis (J. Korean Phys. Soc., (2012), 61, (80)) - Jeong I.-K.; Pandey D. (My University, 2025)
[No abstract available]